Lived experiences of exclusion in the workplace : psychological & behavioural effects - April, Kurt; Dharani, Babar; April, Amanda (International perspectives on equality, diversity and inclusion, 2023)
Lived Experiences of Exclusion in the Workplaceshares the emotional expressions of those who have faced alienation and marginalisation, providing guidance on how to trigger inclusion through various, often simple measures.